Comprehensive analysis of ferroptosis-related gene signatures as a potential therapeutic target for acute myeloid leukemia: A bioinformatics analysis and experimental verification - Zheng, Zhiyuan; Hong, Xiaoying; Huang, Xiaoxue; Jiang, Xiandong; Jiang, He; Huang, Yingying; Wu, Wei; Xue, Yan; Lin, Donghong (Frontiers in Oncology, 2022)
Background: Ferroptosis plays an important role in the development of acute myeloid leukemia (AML). However, the exact role of ferroptosis-related genes in the prognosis of AML patients is unclear. Methods: RNA sequencing data and clinicopathological characteristics of AML patients were obtained from the Cancer Genome Atlas database, and ferroptosis-related genes were obtained from the FerrDb database. Cox regression analysis, the least absolute shrinkage, and selection operators were used to identify ferroptosis-related gene signatures. Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and single-sample gene set enrichment analysis (ssGSEA) were performed to explore the biological functions of the ferroptosis-related genes. Finally, ferroptosis was induced in AML cells by erastin and sulfasalazine for detecting changes in the expression of relevant prognostic genes and exploring the underlying mechanisms by quantitative real-time polymerase chain reaction (qRT-PCR). Results: Seven ferroptosis-related gene signatures (SOCS1, ACSF2, MYB, EIF2AK4, AIFM2, SLC7A11, and GPX4) were identified in the training group, and Kaplan-Meier and Cox regression analyses confirmed that the risk score was an independent prognostic predictor of AML in both the training and validation groups(P<0.05). Functional enrichment analysis revealed that seven ferroptosis-related genes are associated with many immune-related biological processes. Most importantly, both erastin and sulfasalazine can induce ferroptosis in AML cells, and the SLC7A11 and SLC7A11/xCT-GSH-GPX4 pathways may be key genes and potential regulatory pathways in the process of erastin-and sulfasalazine-induced ferroptosis in AML cells. Conclusions: We established a novel signature involving seven ferroptosis-related genes that could accurately predict AML prognosis. In addition, we demonstrated for the first time that the Food and Drug Administration (FDA)-approved drug sulfasalazine can induce ferroptosis in AML cells and that the SLC7A11 and SLC7A11/xCT-GSH-GPX4 pathways may be the key genes and underlying mechanisms in this process, which would provide new insights into strategies for the development of new AML therapies.